KARMA SEBAGAI PRAKSIS PEMBEBASAN DALAM BHAGAVAD GĪTĀ - Arta, I Gede Arya Juni; Rosa, Rosi Ne (Widya Katambung, 2024)
This research is a literature study, using qualitative data. The hermeneutic method was used to analyze data regarding the teaching of karma as a practice of liberation in the text of the Bhagavad Gītā. Where, the Bhagavad Gītā has an important position in Hinduism because it contains the teachings of Brahmavidyā (divine knowledge) and yogaśāstra (yogic knowledge). The Bhagavad Gītā not only guides humans ethically, but also directs humans to carry out practical actions through karma (effort, work, action). In this case, the Bhagavad Gītā makes karma a praxis through the teachings of yoga, as a way to connect oneself (individual soul) with God (Universal Soul). The teaching of karma in the Bhagavad Gītā emphasizes work or actions carried out based on dharma (duty), and awareness of God as the owner of actions (karma). In this case, all the actions he performs will be directed towards God, so that he will no longer be bound by the results of the actions he performs. This is expressed in the Bhagavad Gītā, II.47: karmaṇy evadhikāras te mā phaleṣu kadācana, mā karma-phala-hetur bhūr mā te saṅgo ‘stv karmaṇ. The result of this research is that the Bhagavad Gītā teaches karma as a path to material and spiritual liberation. Where material liberation is interpreted not as an effort to accumulate material possessions, instead it frees humans from the shackles of material attachment by offering all the results of actions or work to God. Complete surrender to God of all karmic results and Unity with God is a form of spiritual liberation.